2001
DOI: 10.1063/1.1331654
|View full text |Cite
|
Sign up to set email alerts
|

Principle of ferroelectric domain imaging using atomic force microscope

Abstract: Effect of Pt bottom electrode texture selection on the tetragonality and physical properties of Ba0.8Sr0.2TiO3 thin films produced by pulsed laser deposition J. Appl. Phys. 112, 044105 (2012) Relationship between dielectric coefficient and Urbach tail width of hydrogenated amorphous germanium carbon alloy films Appl. Phys. Lett. 101, 042109 (2012) Interfacial oxide re-growth in thin film metal oxide III-V semiconductor systemsThe contrast mechanisms of domain imaging experiments assisted by atomic force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
233
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(236 citation statements)
references
References 12 publications
3
233
0
Order By: Relevance
“…39 This electrostatic interaction is comprised of a local contribution due to the tip apex and a nonlocal contribution due to the cantilever. 40 Distinguishing electrostatic forces in a PFM experiment is problematic; however, it can be achieved in SSPM. In SSPM, application of an ac bias to the tip located at 10-100 nm from the surface results in a strong capacitive interaction.…”
Section: Principles Of Pfmmentioning
confidence: 99%
“…39 This electrostatic interaction is comprised of a local contribution due to the tip apex and a nonlocal contribution due to the cantilever. 40 Distinguishing electrostatic forces in a PFM experiment is problematic; however, it can be achieved in SSPM. In SSPM, application of an ac bias to the tip located at 10-100 nm from the surface results in a strong capacitive interaction.…”
Section: Principles Of Pfmmentioning
confidence: 99%
“…The simple formalism for analysis of the electrostatic contribution was established by Hong. 17 However, in the low frequency case, the phase shift between domains is always 180° or 0°, depending on the relative magnitudes of electrostatic and electromechnical contributions. In the dynamic case, the electromechanical and electrostatic contributions to the PFM signal have different phases and the response over c + and c -domains can be written as…”
Section: Iv3 Phase Shifts Between Antiparallel Domainmentioning
confidence: 99%
“…It was recognized that electrostatic tip-surface forces and buckling oscillations of the cantilever can provide significant and in some cases even dominating contributions to the PFM signal. 17,18,19 Imaging ferroelectric materials in the vicinity of a phase transition at small probing biases or imaging of biological systems with weak electromechanical coupling require optimal imaging conditions to be established, and a number of approaches based on using contact resonances in PFM have been suggested. 20,21 Finally, it is recognized that the use of the cantilever coupled with a beam-deflection detection system typical for most commercial AFM s does not allow longitudinal and normal force components to be unambiguously distinguished, 12,22 and it has been suggested that operation at specific frequencies would allow these components to be differentiated.…”
Section: Introductionmentioning
confidence: 99%
“…The PEI image is recorded as an A cos signal. 5 Here, A is the amplitude of the first harmonic signal, which provides information on the magnitude of the piezoelectric coefficient (d 33 ). is the shift in phase between the signal of ac voltage applied and the responding first harmonic, 4 which determines the direction of polarization.…”
Section: Introductionmentioning
confidence: 99%